2011
DOI: 10.1038/hdy.2011.41
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Ireland: revisiting ‘the pygmy shrew syndrome’ using mitochondrial, Y chromosomal and microsatellite markers

Abstract: There is great uncertainty about how Ireland attained its current fauna and flora. Long-distance human-mediated colonization from southwestern Europe has been seen as a possible way that Ireland obtained many of its species; however, Britain has (surprisingly) been neglected as a source area for Ireland. The pygmy shrew has long been considered an illustrative model species, such that the uncertainty of the Irish colonization process has been dubbed 'the pygmy shrew syndrome'. Here, we used new genetic data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…The only securely dated badger fossil in Ireland dates to 1554 BP (P Woodman and M O'Dowd, personal communication) and other fossils are of a Bronze Age context (4000-1500 BP;McCormick, 1999). Therefore, humanmediated introduction(s), which has been reported for other Irish mammals (see, for example, McDevitt et al, 2011), is the most likely scenario and our genetic results support this. Early introductions Figure 6 Inference of the current effective population size, log(N 0 ), of simulated data sets using MSVAR.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The only securely dated badger fossil in Ireland dates to 1554 BP (P Woodman and M O'Dowd, personal communication) and other fossils are of a Bronze Age context (4000-1500 BP;McCormick, 1999). Therefore, humanmediated introduction(s), which has been reported for other Irish mammals (see, for example, McDevitt et al, 2011), is the most likely scenario and our genetic results support this. Early introductions Figure 6 Inference of the current effective population size, log(N 0 ), of simulated data sets using MSVAR.…”
Section: Discussionsupporting
confidence: 79%
“…The question of how the island acquired its fauna and flora has long presented a problem (McDevitt et al, 2011). Using data from a shorter fragment of the control region and six microsatellites, O'Meara et al (2012) recently concluded that badgers have colonised Ireland naturally, but failed to identify how and when this occurred.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the results of our study, it is obvious that high-repetitive-sequence genotypes have a high positive correlation to malignancy grade. McDevitt et al (2011) discovered that Saharan people have a higher frequency of MIF-794CATT promoter microsatellite repetitive sequences. The lowrepetitive-sequence genotype is related to low morbidity of pernicious malaria complications, which suggests that MIF-794CATT 5 is a protective genotype against these complications.…”
Section: Discussionmentioning
confidence: 99%